Exploring the Association between University Students’ Study Skills and Academic Achievement - Hina Zahra; Dr. Mushtaq Ahmed Malik; Dr. Ahmad Bilal Cheema (Research Journal of Social Sciences and Economics Review, 2023)
This study conducted to explore the association among university students’ study skills and academic achievement. The descriptive correlational survey research design was used in the study. All the male and female students enrolled in BS program were the population of this study. The sample selected was 2207 students studying in general public universities of Punjab Pakistan through stratified random sampling technique. With the permission of author, the study skill assessment questionnaire was modified, validated and put through a reliability coefficient .094. Two research hypotheses were formulated and tested through Mean, Standard deviation, ANOVA and Pearson r. The result showed a considerable positive association between study skills and academic achievement of university students. According to the finding of this study, it is recommended that at the time of entrance universities should offer especial training to students so that they can learn or improve their study skills and improve their academic achievement.